Acceptability and willingness of HIV pre-exposure prophylaxis amongst female sex workers in China. Issue 12 (2nd December 2019) - Poon, Adrienne N.; Han, Lifeng; Li, Zhijun; Zhou, Chu; Li, Yan; Huang, Lu; Liao, Meizhen; Shepard, Colin; Bulterys, Marc
ABSTRACT: HIV pre-exposure prophylaxis (PrEP) is a highly effective prevention method. It is an attractive self-initiated approach to reduce the spread of HIV amongst female sex workers (FSW). PrEP, however, has not yet achieved its potential to reduce HIV infections partially due to a general lack of awareness from women who may benefit. Aims of this cross-sectional study of 1, 466 FSW in China were to understand: levels of awareness of and willingness to use PrEP among female sex workers (FSW) in China, and factors contributing to willingness to use PrEP. We found that awareness (10.2%) and willingness (35.5%) to use PrEP were low in our survey areas. Low PrEP willingness is likely reflective of the overall poor knowledge and understanding of HIV risk and prevention. FSW that demonstrated greater HIV knowledge through having been tested or having greater decision-making involvement in condom use were more willing to use PrEP. Study findings may be used to inform future HIV prevention activities, including possible use of PrEP among FSW at higher risk of incident HIV infection in China.